Edukasi Tanaman melalui Program Green Harmony di Kelurahan Situgede, Jawa Barat - Abdillah, Muhammad Reza; Awaliyah, Nursyifa; Rahmawati, Heni; Hasanah, Putri Uswatun; Firdauz, Fairuz Nurul Azhar; Gilbran, Farrel; Brilliansyah, Diandra Nugraha; Syah, Rafi Fabian; Utama, Deo Alif; Farmayanti, Narni (Jurnal Pusat Inovasi Masyarakat, 2024)
The Green Harmony program, implemented by the Thematic Community Service (KKN-T) team from Institut Pertanian Bogor (IPB) in Situgede Village, West Java, aims to enhance community awareness and skills in environmental conservation through plant education. The program comprises three main sub-programs: Green Day, Kisah si Biji, and the Workshop Taman Rumah Ceria, all integrated with the Five Capitals Framework theory. The program's implementation involved collaboration with a local partner, Abdi Tani Farm, and educational outreach to elementary school students and the local community. Green Day focused on land reorganization, Kisah si Biji provided horticultural education to elementary school students, and the Workshop Taman Rumah Ceria offered practical training to residents on techniques for planting and caring for home garden plants. The program successfully engaged 53 children and 19 community members, improving environmental quality and strengthening community knowledge and practices in sustainable gardening. The education and empowerment provided through Green Harmony not only positively impacted the physical environment but also inspired the community to continue environmental stewardship and more effectively utilize their home gardens.